Acute Bronchiolitis in Term Newborns Following Relaxation in COVID-19 Appropriate Behavior - Qureshi, Umar Amin; Bhat, Abdus Sami; Lone, Mohd Suhail; Jan, Muzafar; Wani, Nisar Ahmad; Shah, Mubashir Hassan (Journal of Pediatric Infectious Diseases, 2023)
Objective Neonatal bronchiolitis is not well characterized. We studied the profile of acute bronchiolitis in term newborns during a respiratory syncytial virus (RSV) surge following relaxation in coronavirus disease 2019 (COVID-19) appropriate behavior.Methods This was a retrospective descriptive study performed in the neonatology division of a tertiary care pediatric hospital at Srinagar, Jammu and Kashmir, India. Term neonates (born at ≥37 completed gestational weeks) from 7 up to 28 days of life admitted with bronchiolitis over a 1-month period (November 2021) were included.Results Out of total 480 neonatal admissions over a month, 35 (7%) had acute bronchiolitis. Eight neonates were excluded. Out of 27 included neonates, 13 were males. Mean age at presentation was 20 days. All neonates were born at term (≥37 completed gestational weeks). Cough (26), rapid breathing (20), and lower chest indrawing (20) were the predominant presenting features. Median SPO2 was 87% (interquartile range 85–92%). Fourteen (52%) neonates needed admission to neonatal intensive care unit. Respiratory support was needed in the form of oxygen through nasal prongs in 24 (89%) newborns. Heated humidified high-flow nasal cannula (HHHFNC) and bubble continuous positive airway pressure were used in five neonates each. Two neonates were mechanically ventilated. The mean duration of the hospital stay was 6.2 days. All neonates survived.Conclusion A series of 27 term neonates with bronchiolitis during an RSV surge is reported in the aftermath of lifting of COVID-19 restrictions. Many of these neonates were sick enough to require significant respiratory support. The outcome was good in all neonates.
Keywords: acute bronchiolitis; neonates; RSV; respiratory support